T.S. Eliot and the Essay: From the Sacred Wood to the Four Quartets. By G. Douglas Atkins - Whistler, Daniel (Literature and theology, 2011)
T.S. Eliot and the Essay, the final work in Atkins’ trilogy on the essay form, is both an application of the author's theory of the essay to Eliot's writings and also a demonstration of the ways in which the essay has been ‘turned’ or mutated during the 20th century. T.S. Eliot and the Essay therefore defends two theses: Eliot's essays are representative of the essay as such; Eliot's essays are peculiar—they turn away from the reflective tradition of Montaigne and Wordsworth in favour of a neoclassical style., The second thesis is the less controversial, since Eliot is consciously reactionary in his choice of models for his prose. In parallel to his genealogy of the disassociation of sensibility, Eliot recovers an alternative, pre-romantic form of the essay in the works of Dryden and Pope.